Olga Fečová: Den byl pro mě krátkej. Paměti hrdé Romky: Praha: KHER, Paseka, 2022, 223 s., ISBN 978-80-7637-334-1 (Paseka), ISBN978-80-87780-31-2 (KHER) - Zdařilová, Eva (Romano džaniben, 2023)
RECENZE